Interest of the Algerian diaspora for entrepreneurship in homeland: proposal of a model for its concretisation - A. Haddad; R. Lassoued (Вестник университета)
In the era of globalisation, diaspora is seen as a driving force for economic development in the countries of origin and for positive changes in the host countries. The Algerian diaspora represents a real opportunity and potential of entrepreneurs that are not exploited. This article attempts to explore the factors that encourage or hinder the entrepreneurial activities of the Algerian diaspora in its country of origin through a field survey based on 142 entrepreneurs from the studied diaspora. To do this, a logistic econometric modelling has been implemented to explain the entrepreneurial event (business creation), and the explanatory variables are the following factors: psychological (experience, training), contextual (discrimination, opportunities, and patriotism) sociological (help of relatives and other contacts) and economic (personal resources and those of the state). It appears that the probability of the project in Algeria is stronger as its leader from the Algerian diaspora has a great entrepreneurial potential and financial means, is an opportunist and patriot, benefits from the help of the state and knows how to activate, in case of difficulties, their personal contacts.